Dissection of the contributions of cyclophilin genes to development and virulence in a fungal insect pathogen. (2nd June 2016) - Zhou, Yonghong; Keyhani, Nemat O.; Zhang, Yongjun; Luo, Zhibing; Fan, Yanhua; Li, Yujie; Zhou, Qiaosheng; Chen, Jianjun; Pei, Yan
Summary: Cyclophilins are ubiquitous proteins found in all domains of life, catalyzing peptidyl‐prolyl cis‐trans isomerization (PPIase activity) and functioning in diverse cellular processes. The filamentous insect pathogenic fungus, Beauveria bassiana, contains 11 cyclophilin genes whose roles were probed via individual gene knockouts, construction of over‐expression strains, and a simultaneous gene knockdown strategy using tandem SiRNA. Mutants were examined for effects on conidiation, hyphal growth, cyclosporine and stress resistance, and insect virulence. BbCypA was found to be the most highly expressed cyclophilin during growth and purified recombinant BbCypA displayed cyclosporine sensitive PPIase activity. Except for Δ BbCypA, targeted gene knockouts or overexpression of any cyclophilin resulted in temperature sensitivity (TS). Specific cyclophilin mutants showed impaired hyphal growth and differential effects on conidiation and cyclosporine resistance. Insect bioassays revealed decreased virulence for two cyclophilins (Δ BbCypE and Δ BbCyp6 ) and the simultaneous gene knockdown mutant constructs ( SiRNA30 ). The BbSiRNA30 strains were unaffected in growth, conidiation, or under osmotic or cell wall perturbing stress, but did show increased resistance to cyclosporine and a TS phenotype. These results revealed common and unique roles for cyclophilins in B. bassiana and validate a method for examining the effects of multi‐gene families via simultaneous gene knockdown.